Developing Digital Worksheet Based on Project Based Learning Model to Enhance Writing Ability of Junior High School Student - Satria, Dessy; Zulhiddah, Zulhiddah; Zulkifli, Nur Aisyah (Innovative: Journal Of Social Science Research, 2025)
This research tries to integrate student worksheets and technology in the form of a digital worksheet design based on a project-based learning to improve the writing ability of grade 7 students. The use of technology that is integrated with worksheets is a development in the world of education that is inevitable according to the times. Using the ADDIE method, this study designed a project-based learning-based digital worksheet on students' writing skills using the Canva platform. With a quantitative approach in determining the effectiveness and practically of a digital worksheet. From the calculation of the results, it shows that with a sample of 106 people, the 5% r table is 0.632, meaning that the total is 0.503 > 0.195. And it was found that if the 1% r table is 0.256, it means 0.503 > 0.765. So, it can be concluded that the digital worksheets used are effective. In addition to being effective, the application of digital worksheets also improves students' writing skills. We are 95% confident that post-test scores are higher than pretest scores, with an average difference between 10,359 and 13,509), This indicates an improvement in overall learning outcomes